Convergence of Nonstationary Iterative Methods for Solving Singular Linear Equations with Index One. (2nd November 2017) - Ma, Haifeng; Xiao, Cheng
ABSTRACT: In this paper, we investigate the nonstationary iterative scheme for solving consistent singular linear system with index one. We utilize the group inverse to present a sufficient condition for the convergence of the nonstationary iterative method. Our result extends the known results of the stationary iterative scheme. Finally, we present a sufficient condition for the multisplitting algorithm and provide numerical examples to illustrate the advantages of nonstationary method.